Preparation method and application of iridium oxide oxygen evolution electrocatalyst anchored by titanium oxygen species on surface
By using the iridium oxide oxygen evolution electrocatalyst anchored by surface titanium oxide species in PEM electrolytic technology, the problems of poor stability of the anode catalyst and insufficient thickness of the catalytic layer are solved, and efficient and stable hydrogen production process and cost reduction are achieved.
Patent Information
- Application Number
- CN202411913205.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-12-24
AI Technical Summary
In the existing PEM electrolytic technology, the anode catalyst has poor stability and it is difficult to build an anode electrode structure with an ultra-thin catalytic layer, which limits the reduction of hydrogen production efficiency and cost.
The electrochemical oxidation of the surface titanium nitride-supported metal iridium cluster precatalyst is prepared to achieve spontaneous thickening and structural uniformity of the catalyst.
The catalyst exhibits high catalytic activity and stability in the oxygen evolution reaction, and can achieve large-scale industrial applications under low iridium load, reduce hydrogen production costs, and increase the life of the electrode material.
Smart Images

Figure CN119913552A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalysts, and relates to a method for preparing an iridium oxide oxygen evolution electrocatalyst with titanium oxide species anchored on its surface. It also relates to its use as an electrocatalyst for oxygen evolution reaction in the preparation of an acidic electrolyte, and its use as a PEM anode in PEM water electrolysis. It also has potential application value in other fields such as energy development and environmental protection. Background Art
[0002] Renewable energy water electrolysis hydrogen production is the technology with the lowest carbon emissions among the current hydrogen source solutions. 60% to 80% of its hydrogen production cost comes from the electrolyzer; among them, efficient, stable and cheap catalysts can reduce electrolysis energy consumption and extend device life, which is a difficult problem in the development of this technology. Acidic medium PEM water electrolysis technology is an ideal means of efficiently preparing high-purity hydrogen. It has high energy conversion efficiency, high hydrogen production rate, and high hydrogen purity. At the same time, it has the dynamic / static response characteristics of a fast hydrogen production system under complex working conditions, which meets the use requirements of fluctuating power supply water electrolysis hydrogen production system.
[0003] The PEM anode oxygen evolution catalyst material directly affects the device efficiency and cost. Currently, only high-load Ir-based materials can work stably on commercial equipment, and the development of low-Ir-load anode electrodes is still the key to restricting the large-scale deployment of PEM water electrolysis. New anode materials and corresponding membrane electrodes that can control stable working conditions can be used to build high-performance, long-life PEM water electrolysis hydrogen production equipment, realize large-scale, low-cost hydrogen production processes, and are expected to promote the cost reduction and efficiency improvement and industrialization process of large-scale PEM hydrogen production. Summary of the invention
[0004] The present invention is aimed at the above problems, and aims to provide a preparation method and application of iridium oxide oxygen evolution electrocatalyst anchored with titanium oxide species on the surface, so as to solve the problems of poor stability of anode catalyst and difficulty in constructing an anode electrode structure with an ultra-thin catalytic layer in the existing PEM water electrolysis technology. The catalyst material has good economic efficiency, high oxygen evolution activity, simple preparation method and application potential.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is summarized as follows: the catalyst is obtained by electro-oxidation of a metal iridium cluster pre-catalyst supported by titanium nitride, wherein the surface titanium oxide species are obtained by electrochemical reconstruction of titanium nitride, and iridium oxide is obtained by electro-oxidation of the metal iridium cluster.
[0006] The specific technical solutions adopted are as follows:
[0007] In a first aspect, the present invention provides a method for preparing an iridium oxide oxygen evolution electrocatalyst anchored with titanium oxide species on the surface, comprising the following steps:
[0008] A. Preparation of precatalyst
[0009] The titanium nitride, surfactant and iridium hydrochloric acid mixed solution were ultrasonically mixed, and then heated in an oil bath at 120°C while being stirred for reaction; after the reaction was completed, the mixture was cooled to room temperature, the black product was centrifuged, washed with an organic solvent for multiple times, and dried in a vacuum oven at 60°C to obtain a black powder which was a metal iridium cluster precatalyst supported by titanium nitride;
[0010] B. Pre-catalyst electro-oxidation
[0011] Using titanium nitride supported metal iridium cluster precatalyst as anode and Pt / C catalyst as cathode, electro-oxidation was carried out in a PEM electrolyzer to obtain an iridium oxide oxygen evolution catalyst with surface titanium oxide species anchored.
[0012] Preferably, the preferred process conditions of the above steps are as follows:
[0013] (1) Step A
[0014] The preparation method of a titanium nitride, surfactant, and iridium salt mixed solution comprises the following steps: (a) accurately weighing titanium nitride and P123 surfactant in a feed mass ratio of 1:2, dispersing them in ethylene glycol, and ultrasonically homogenizing them; (b) accurately weighing iridium hydrochloric acid, dissolving them in ethylene glycol, and ultrasonically obtaining a homogenous solution; (3) mixing the solutions in steps (1) and (2), and continuing ultrasonication for half an hour. The feed molar ratio of titanium nitride to iridium hydrochloric acid is 0.65:0.1-0.4.
[0015] More preferably, the average size of titanium nitride is 20 nm; and the iridium hydrochloric acid is selected from chloroiridic acid.
[0016] When the reaction is carried out, the mixture is heated in an oil bath at 120°C for 3 hours while being stirred at a speed of 1200 rpm.
[0017] After the reaction, the black product was separated by centrifugation, washed with anhydrous ethanol for several times, and finally dried in a vacuum oven at 60° C. for 12 hours to obtain a titanium nitride-supported metal iridium cluster precatalyst.
[0018] (2) Step B
[0019] The spray loading of the precatalyst was 0.28 mg cm -2 ; The cathode catalyst is 40wt% Pt / C, and the Pt spray loading is 0.4mg Pt cm -2 ; The electro-oxidation conditions were 1A·cm in a PEM electrolyzer -2 After 24 h of electrooxidation, titanium nitride was oxidized and dissolved to obtain an iridium oxide oxygen evolution catalyst anchored by surface titanium oxide species.
[0020] In a second aspect, the present invention provides an iridium oxide oxygen evolution electrocatalyst with titanium oxide species anchored on its surface, which is prepared by the above method.
[0021] The X-ray diffraction pattern shows that the catalyst exists in two physical phases, metallic iridium and titanium nitride; the energy dispersive X-ray spectrum shows that titanium oxide species are mainly distributed on the surface of iridium oxide; according to the high-angle annular dark field-scanning transmission electron microscope image, it can be seen that iridium oxide is amorphous, with titanium species anchored on the surface, which appear as atoms with relatively dark contrast.
[0022] The above catalyst was prepared into anode material for electrocatalysis. The results showed that after electro-oxidation, the thickness of the membrane electrode anode catalyst layer increased significantly, indicating that the initially prepared ultra-thin catalyst layer can spontaneously thicken during the electro-oxidation process and tend to be uniform and porous.
[0023] The material of the invention can be applied to a proton exchange membrane (PEM) water electrolysis tank under acidic electrolyte conditions.
[0024] It was prepared into anode electrode material for proton exchange membrane electrolyzer, and full cell test was carried out in proton exchange membrane acidic water electrolyzer to simulate industrial water electrolysis environment. The results showed that the catalyst as anode in PEM electrolyzer reached 1.0 and 2.0A·cm -2 The current density required was 1.6 and 1.8 V, respectively, which was 60 and 140 mV lower than that of titanium dioxide as a carrier. At the same time, the electrode material can operate efficiently and stably for 200 h without obvious attenuation.
[0025] Therefore, the third aspect of the present invention provides the use of the above-mentioned iridium oxide oxygen evolution electrocatalyst anchored with titanium oxide species on the surface in the preparation of an acidic electrolytic oxygen evolution electrode.
[0026] In a fourth aspect, the present invention provides an acidic electrolytic oxygen evolution anode electrode, comprising an anode carrier and a catalyst material loaded thereon, wherein the catalyst material is an iridium oxide oxygen evolution electrocatalyst anchored with a surface titanium oxide species prepared by any of the methods described above.
[0027] Preferably, the acidic electrolytic oxygen-splitting anode electrode is the anode of a PEM electrolyzer.
[0028] In a fifth aspect, the present invention provides a method for electrolyzing water, using the above-mentioned electrolytic oxygen-splitting anode electrode as a PEM electrolysis anode.
[0029] Preferably, the electrolyte is 0.5M HClO4 solution or deionized water.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The present invention uses titanium nitride-supported metal iridium clusters as pre-catalysts and prepares a novel surface titanium oxide species-anchored iridium oxide oxygen evolution electrocatalyst through an electrochemical oxidation reconstruction method. The catalyst exhibits high catalytic activity and significantly enhanced stability in the oxygen evolution reaction.
[0032] (2) The catalyst provided by the present invention is used as an anode catalyst in a PEM water electrolyzer. The initial electrode with an ultra-thin catalyst layer can be spontaneously converted into a catalyst layer structure with suitable thickness, uniform structure and good mechanical stability through the self-thickening effect of the pre-catalyst during the electro-oxidation process, thereby avoiding the problems of uneven catalyst distribution, poor contact, poor local conductivity and unstable structure caused by insufficient thickness of the existing anode ultra-thin catalyst layer. Therefore, it is easier to achieve large-scale industrial applications at ultra-low iridium loading.
[0033] (3) The catalyst provided by the present invention is simple to prepare, the raw materials for preparation are environmentally friendly, the use of harmful solvents is reduced, the energy consumption of the reaction process is low, and the prepared catalyst is evenly dispersed, highly practical, easy to promote, and easy to achieve large-scale industrial preparation and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is the X-ray diffraction pattern of the titanium nitride-supported metal iridium cluster precatalyst prepared in Example 1.
[0035] Figure 2 This is a high-angle annular dark field-scanning transmission electron microscope image of iridium oxide anchored by surface titanium oxide species prepared in Example 1.
[0036] Figure 3 This is the energy dispersive X-ray spectrum of the iridium oxide anchored with surface titanium oxide species prepared in Example 1.
[0037] Figure 4 This is a scanning electron microscope cross-sectional view of the titanium nitride-supported metal iridium cluster precatalyst in Example 1 and the surface titanium oxide species-anchored iridium oxide membrane electrode anode catalyst layer obtained after electro-oxidation.
[0038] Figure 5 This is a comparison diagram of polarization curves of the iridium oxide catalyst anchored with surface titanium oxide species prepared in Example 1 and the catalyst prepared in Comparative Example 2 as anode catalysts for PEM water electrolysis.
[0039] Figure 6 The 1Acm of iridium oxide anchored with titanium oxide species prepared in Example 1 as anode catalyst for PEM water electrolysis -2 Stability test results. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] The "range" disclosed herein is in the form of a lower limit and an upper limit. It can be one or more lower limits, and one or more upper limits, respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges that can be defined in this way are inclusive and combinable, i.e., any lower limit can be combined with any upper limit to form a range. For example, a range of 100 to 140 and 500 to 900 is listed for a particular parameter, and it is understood that a range of 100 to 140 and 500 to 900 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum ranges 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 2, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5.
[0042] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations.
[0043] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.
[0044] 1. Preparation of Catalyst Materials
[0045] Example 1
[0046] The preparation method of the iridium oxide oxygen evolution electrocatalyst anchored with titanium oxide species on the surface provided in this embodiment comprises the following steps:
[0047] (1) Accurately weigh 40 mg of titanium nitride and 80 mg of P123 surfactant and disperse them in 10 mL of ethylene glycol, and mix them by ultrasonication.
[0048] (2) Accurately weigh 122.1 mg of chloroiridic acid and dissolve it in 10 mL of ethylene glycol, and ultrasonicate to obtain a uniform solution;
[0049] (3) The solutions in steps (1) and (2) were mixed and placed in a 50 ml flask. After continuing ultrasonication for half an hour, the mixture was heated in an oil bath at 120° C. for 3 hours while stirring at 1200 rpm.
[0050] (4) After the reaction is completed, the mixture is cooled to room temperature, the black product is separated by centrifugation, washed with anhydrous ethanol for multiple times, and finally dried in a vacuum oven at 60° C. for 12 hours to obtain a titanium nitride-supported metal iridium cluster precatalyst.
[0051] (5) Using titanium nitride-supported metal iridium cluster precatalyst as the anode, electro-oxidation was carried out in a PEM electrolyzer with a spray loading of 0.28 mg cm -2 ; The cathode catalyst is 40wt% Pt / C, and the Pt spray loading is 0.4mg Pt cm -2 , using DuPont 212 proton exchange membrane, electrode area 5cm 2 The test temperature was 80 °C and the electro-oxidation condition was 1 A·cm -2 , 24h, through titanium nitride oxidation dissolution, an iridium oxide oxygen evolution catalyst anchored by surface titanium oxide species was obtained.
[0052] Example 2
[0053] The operating steps of Example 1 were repeated, except that in step (2), the mass of chloroiridic acid was 40.7 mg.
[0054] Example 3
[0055] The operating steps of Example 1 were repeated, except that in step (2), the mass of chloroiridic acid was 81.4 mg.
[0056] Example 4
[0057] The operating steps of Example 1 were repeated, except that in step (2), the mass of chloroiridic acid was 162.8 mg.
[0058] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
[0059] Comparative Example 1
[0060] The operating steps of Example 1 were repeated, except that titanium nitride was not added in the preparation of the precursor solution.
[0061] Comparative Example 2
[0062] The operating steps of Example 1 were repeated, except that titanium dioxide was added instead of titanium nitride in the preparation of the precursor solution.
[0063] 2. Performance Characterization Test
[0064] Figure 1 This is the X-ray diffraction spectrum of the titanium nitride-supported metal iridium cluster precatalyst prepared in Example 1. The electrocatalyst exists in two physical phases, namely metal iridium and titanium nitride.
[0065] Figure 2 This is a high-angle annular dark field-scanning transmission electron microscope image of iridium oxide anchored by surface titanium oxide species prepared in Example 1. Figure 2 It can be seen that iridium oxide is amorphous, with titanium species anchored on the surface, appearing as atoms with relatively dark contrast.
[0066] Figure 3 This is the energy dispersive X-ray spectrum of the surface titanium oxide species anchored iridium oxide prepared in Example 1. Figure 3 It can be seen that titanium oxide species are mainly distributed on the surface of iridium oxide.
[0067] Figure 4 The scanning electron microscope cross-sectional view of the titanium nitride supported metal iridium cluster precatalyst and the surface titanium oxide species anchored iridium oxide membrane electrode anode catalyst layer obtained after electro-oxidation in Example 1. Figure 4 It can be seen that after electro-oxidation, the thickness of the membrane electrode anode catalyst layer increased significantly, indicating that the initially prepared ultra-thin catalyst layer can spontaneously thicken during the electro-oxidation process and tend to be uniform and porous.
[0068] 3. Electrochemical performance test
[0069] The electrocatalytic performance of iridium oxide anchored with titanium oxide species on the surface was tested using a PEM electrolyzer system. The catalyst prepared in Example 1 was subjected to a PEM electrolyzer polarization curve test and the electrocatalytic performance was tested at 1 A·cm -2 The stability of the assembled electrolytic cell was tested under different current densities.
[0070] Figure 5 This is a comparison of polarization curves of the iridium oxide catalyst anchored with titanium oxide species prepared in Example 1 and the catalyst prepared in Comparative Example 2 as anode catalysts for PEM water electrolysis. Figure 5 It can be seen that the catalyst prepared in Example 1 can reach 1.0 and 2.0 A·cm as anode in the PEM electrolyzer. -2 The current density required was 1.6 and 1.8 V, respectively, which was 60 and 140 mV lower than that of Comparative Example 2.
[0071] Figure 6 The 1A·cm of iridium oxide anchored with titanium oxide species prepared in Example 1 as anode catalyst for PEM water electrolysis -2 Stability test results. Figure 6It can be seen that the electrode material prepared in Example 1 can operate efficiently and stably for 200 hours without obvious attenuation.
[0072] The preferred embodiments of the present invention have been specifically described above, but the present invention is not limited to the embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the present invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.
Claims
1. A method for preparing an iridium oxide oxygen evolution electrocatalyst anchored with titanium oxide species on the surface, characterized in that: The steps include: A. Preparation of precatalyst The titanium nitride, surfactant and iridium hydrochloric acid mixed solution were ultrasonically mixed, and then heated in an oil bath at 120°C while being stirred for reaction; after the reaction was completed, the mixture was cooled to room temperature, the black product was centrifuged, washed with an organic solvent for multiple times, and dried in a vacuum oven at 60°C to obtain a black powder which was a metal iridium cluster precatalyst supported by titanium nitride; B. Pre-catalyst electro-oxidation Using titanium nitride supported metal iridium cluster precatalyst as anode and Pt / C catalyst as cathode, electro-oxidation was carried out in a PEM electrolyzer to obtain an iridium oxide oxygen evolution catalyst with surface titanium oxide species anchored.
2. The preparation method according to claim 1, characterized in that: in, In step A, the preparation method of the mixed solution of titanium nitride, surfactant and iridium hydrochloric acid comprises the following steps: (a) accurately weighing titanium nitride and surfactant in a feed mass ratio of 1:2, dispersing them in ethylene glycol respectively, and ultrasonically homogenizing; (b) accurately weighing iridium hydrochloric acid and dissolving it in ethylene glycol, and ultrasonically obtaining a homogenous solution; (c) mixing the solutions in steps (1) and (2), and continuing ultrasonication for half an hour; When the reaction is carried out, the mixture is heated in an oil bath at 120°C for 3 hours while being stirred at a speed of 1200 rpm. After the reaction, the black product was separated by centrifugation, washed with anhydrous ethanol for several times, and finally dried in a vacuum oven at 60° C. for 12 hours to obtain a titanium nitride-supported metal iridium cluster precatalyst.
3. The preparation method according to claim 2, characterized in that: in, The surfactant is selected from P123 surfactant, the average size of titanium nitride is 20nm; the iridium hydrochloric acid is selected from chloroiridic acid, In step (c), the molar ratio of titanium nitride to iridium hydrochloric acid is 0.65:0.1-0.
4.
4. The preparation method according to claim 1, characterized in that: in, In step B, the spray loading of the precatalyst was 0.28 mg cm -2 ; The cathode catalyst is 40wt% Pt / C, and the Pt spray loading is 0.4mg Pt cm -2 ; The electro-oxidation conditions were 1A·cm in a PEM electrolyzer -2 After 24 h of electrooxidation, titanium nitride was oxidized and dissolved to obtain an iridium oxide oxygen evolution catalyst anchored by surface titanium oxide species.
5. An iridium oxide oxygen evolution electrocatalyst anchored with titanium oxide species on the surface, characterized in that: The method is prepared by any one of claims 1 to 4.
6. Use of the iridium oxide oxygen evolution electrocatalyst anchored with titanium oxide species on the surface as claimed in claim 5 in the preparation of an acidic electrolytic oxygen evolution electrode.
7. An acidic electrolytic oxygen anode electrode, characterized in that: The invention comprises an anode carrier and a catalyst material loaded thereon, wherein the catalyst material is an iridium oxide oxygen evolution electrocatalyst anchored with a surface titanium oxide species prepared by the method according to any one of claims 1 to 4.
8. The acidic electrolytic oxygen-splitting anode electrode according to claim 7, characterized in that: The acidic electrolytic oxygen-splitting anode electrode is the anode of a PEM electrolyzer.
9. A method for electrolyzing water, characterized in that: The acidic electrolytic oxygen-splitting anode electrode according to claim 7 or 8 is used as the PEM electrolysis anode.
10. The method for electrolyzing water according to claim 9, characterized in that: in, The electrolyte is 0.5M HClO4 solution or deionized water.
Citation Information
Patent Citations
Low-iridium electrolyzed water catalyst as well as preparation method and application thereof
CN115369422A
Catalyst for PEM water electrolysis, preparation method and application thereof
CN118547328A
Oxygen evolution catalyst for PEM water electrolysis as well as preparation method and application of oxygen evolution catalyst
CN118563359A